Cardiac myosin light chain phosphorylation and inotropic effects of a biased ligand, TRV120023, in a dilated cardiomyopathy model. (4th June 2015) - Tarigopula, Madhusudhan; Davis, Robert T.; Mungai, Paul T.; Ryba, David M.; Wieczorek, David F.; Cowan, Conrad L.; Violin, Jonathan D.; Wolska, Beata M.; Solaro, R. John
Abstract: Aims: Therapeutic approaches to treat familial dilated cardiomyopathy (DCM), which is characterized by depressed sarcomeric tension and susceptibility to Ca 2+ -related arrhythmias, have been generally unsuccessful. Our objective in the present work was to determine the effect of the angiotensin II type 1 receptor (AT1R) biased ligand, TRV120023, on contractility of hearts of a transgenic mouse model of familial DCM with mutation in tropomyosin at position 54 (TG-E54K). Our rationale is based on previous studies, which have supported the hypothesis that biased G-protein-coupled receptor ligands, signalling via β-arrestin, increase cardiac contractility with no effect on Ca 2+ transients. Our previous work demonstrated that the biased ligand TRV120023 is able to block angiotensin-induced hypertrophy, while promoting an increase in sarcomere Ca 2+ response. Methods and results: We tested the hypothesis that the depression in cardiac function associated with DCM can be offset by infusion of the AT1R biased ligand, TRV120023. We intravenously infused saline, TRV120023, or the unbiased ligand, losartan, for 15 min in TG-E54K and non-transgenic mice to obtain left ventricular pressure–volume relations. Hearts were analysed for sarcomeric protein phosphorylation. Results showed that the AT1R biased ligand increases cardiac performance in TG-E54K mice in association with increased myosin light chain-2 phosphorylation. Conclusion: Treatment of mice with an AT1R biased ligand, acting via β-arrestin signalling, is able to induce an increase in cardiac contractility associated with an increase in ventricular myosin light chain-2 phosphorylation. AT1R biased ligands may prove to be a novel inotropic approach in familial DCM.